Investigation on passive pile responses subject to adjacent tunnelling in anisotropic clay - Li, Yongqin; Zhang, Wengang (Computers and geotechnics, 2020)
Pile’s excessive internal forces and displacements induced by adjacent tunnelling can cause serious serviceability problems for infrastructure aboveground, emphasizing the necessity for predicting the pile responses during the preliminary tunnel design. This study present extensive finite element (FE) analysis to investigate the passive pile’s lateral stress and deformation development using a centrifuge test study as model validation. An anisotropic soil constitutive model NGI-ADP is employed to simulate the clay’s behaviour, filling the gap of capturing soil’s stress-induced anisotropy characteristics in exploring tunnel-soil-pile interaction problem. For further exploration of construction factors’ effects, the parametric analysis for tunnelling locations, pile service situations and the anisotropic degree are conducted, assessing their influences on tunnelling-induced pile deflection, bending moment, and shaft resistance. The results show despite the conventional ignorance of the soil’s intrinsic anisotropy, it stands as a contributing factor in determining the pile behaviour since the soil displacement field is inevitably dependent on this inherent characteristic. For various pile properties and tunneling locations, some useful suggestions for constructions are drawn to avoid severe damage within the pile body. Moreover, the effect of the pile’s vertical working is revealed to be not critical to its stability when the pile was subject to surrounding disturbance.